Bridging the Methodological Gap: Emic and Etic Paradigms in Evolving the Living Hadith Studies: Menjembatani Kesenjangan Metodologis: Paradigma Emik dan Etik dalam Perkembanganan Studi Living Hadis - Rizkiy, M. Inul (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The study of living hadith, while demonstrating the advancement of hadith scholarship, nonetheless leaves considerable room for further development. Moreover, researchers' awareness of the reality of hadith as a foundation for rituals still requires methodological strengthening, particularly concerning whether interpretations arise from the reception of practitioners within the tradition (emic) or from the researcher's own analysis (etic). This article aims to explore more deeply the concepts of emic and etic in living hadith studies, as well as their application in this field of research. Concretely, two fundamental questions form the basis of this study: First, how are emic and etic constructed in living hadith research? Second, what are the patterns of distribution of emic and etic within the dynamics of living hadith studies? These questions are examined using a systematic literature review approach, with data sourced from Google Scholar using the keywords